2011
DOI: 10.1002/ppul.21423
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and life satisfaction in parents caring for children with cystic fibrosis

Abstract: Results More than one-third (37.2%) of parents showed elevated levels of anxious symptoms, compared to 18.9% of a population sample (p≤.001) and significantly more parents reported elevated levels of depressive symptoms compared to a community sample (28% vs. 21%, p=.01). Higher levels of anxious and depressive symptoms were associated with lower life satisfaction (p<.001).Conclusions High levels of anxious and depressive symptoms among parents of children with CF suggested that annual symptom screening is war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 41 publications
3
52
1
5
Order By: Relevance
“…A significant proportion of mothers of children with CF show depressive symptoms soon after the diagnosis of their child, independent of the degree of the child's illness [108], and many parents report significant psychological distress years afterward [109,110]. Recent studies have shown the prevalence of anxiety and depression in patients with CF and their parents to be as high as 30%, significantly higher than in the general population [111].…”
Section: Psychological Functioningmentioning
confidence: 98%
“…A significant proportion of mothers of children with CF show depressive symptoms soon after the diagnosis of their child, independent of the degree of the child's illness [108], and many parents report significant psychological distress years afterward [109,110]. Recent studies have shown the prevalence of anxiety and depression in patients with CF and their parents to be as high as 30%, significantly higher than in the general population [111].…”
Section: Psychological Functioningmentioning
confidence: 98%
“…A detailed description of the complete German sample, which proved to be representative of the German CF population, has been published elsewhere [15,18].…”
Section: Participantsmentioning
confidence: 99%
“…Parent caregivers of children with CF have to face multiple challenges while caring for their child and their own health and psychological well-being is put at risk, e.g., in terms of higher rates of anxiety and depression compared to the general population [16][17][18]. During adolescence parents are challenged with decreasing parental control over the treatment regimen and adherence problems, paired with growing concern about their child's health status.…”
Section: Introductionmentioning
confidence: 98%
“…Bu çalışmalarda annelerde %20-53 arasında depresyon/depresif belirti ve %18-57 arasında anksiyete bozukluğu/belirtileri bildirilmiştir (2,5,6,10,28). Bizim araştırmamızda KF grubunda %28.6 oranında psikopatoloji ile uyumlu puan alan anne bulunmaktadır.…”
Section: Bulgularunclassified